If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x-4x+12=2(12-x)
We move all terms to the left:
-x-4x+12-(2(12-x))=0
We add all the numbers together, and all the variables
-x-4x-(2(-1x+12))+12=0
We add all the numbers together, and all the variables
-5x-(2(-1x+12))+12=0
We calculate terms in parentheses: -(2(-1x+12)), so:We get rid of parentheses
2(-1x+12)
We multiply parentheses
-2x+24
Back to the equation:
-(-2x+24)
-5x+2x-24+12=0
We add all the numbers together, and all the variables
-3x-12=0
We move all terms containing x to the left, all other terms to the right
-3x=12
x=12/-3
x=-4
| -3x+10(2x/3)=-11 | | 5(x–6)=4x+4. | | r=4(3.14)(16) | | b/53=3 | | 4x+4=6x–3 | | -3(x+2)=3(x+4) | | -12-14v=-20v | | 9(b+0.5=9b+4.5 | | 0.18(y-2)+0.06y=0.14y-0.6 | | 3a+5=75^2 | | a-73=109 | | 3/4x-2=2/4x+6 | | 4(2x-5)=5x-9 | | -8+1100=y | | 2(x^2-1)=98.x | | .25p=5.50 | | 25p=5.50 | | -33+2x=4 | | 8*n/4=36 | | 15x-12=-3 | | 6.2n=5.6n-2.04 | | 8(2x+3)-9x+17=-8 | | -100x2+55x+3=50x2-55x+23 | | .4b+5=1+5b4b+5=1+5b | | 5/8-3/8s=2-s | | 5x^+14x=x+6 | | 10-10v=-8-v | | (5^x-25)^6-23=37 | | 16+2x=7x-4 | | 12.7+4.9=y | | 4x-10=22x= | | 4x^-24=20x |